Suez : The Seven Day War - Barker, A. J. (London Faber and Faber LTD, 1964)
British Colonel's first-hand analysis of the military operations and make-shift strategy employed in the Anglo-French and Israeli expedition against Egypt in 1956
Include Illustration, Appendix and Index
Keywords: Egypt -- Egypt--Suez Canal -- Intervention in Egypt (1956)